Global One Health Index Report 2022 - Zhou, Xiao-Nong.; Guo, Xiaokui; Zhang, Xiaoxi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This Open Access book intends to report the new results of the Global One Health Index (GOHI). The content of this book underlines the functions and importance of developing the evaluation tool (GOHI) for global One Health practice, shows the results of GOHI score in 160 countries/territories and key findings in details, and provides different policy recommendations to UN agencies, countries, and communities to promote the wide application of the One Health approach. A pilot study was conducted in 2021, and its related publications are collected in one section of the book. The book is likely to be of interest to researchers, practitioners, policy-makers, and stakeholders in applying One Health who wish to learn about the development, results, key findings, and policy recommendations of GOHI study.
Chapter 1. Executive Summary -- Chapter 2. Methodology -- Chapter 3. GOHI Dashboard -- Chapter 4. Special Reports -- Chapter 5. Findings & Recommendations -- Appendix.
Keywords: Public health; Medicine, Preventive; Health promotion; Medical policy; Public Health; Health Promotion and Disease Prevention; Health Policy